STUDENTS’ PERCEPTIONS OF THE USE OF DIGITAL AND PRINTED TEXTBOOKS - Elyan Rizky; Hesti Wahyuni Anggraini (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2023)
The introduction of technology has changed how students perceive and prefer learning and knowledge acquisition, specifically in choosing types of textbooks. In addition to the printed textbook, many textbooks are now also available in digital formats. The purposes of this study were, firstly, to determine how students perceived digital and printed textbooks and secondly to know their reading preference. Using purposive random sampling, qualitative data was obtained through interviews with six students from three different semesters of the English Education Study Program of Sriwijaya University Palembang, selected on the basis of their English ability level. The findings were analysed in terms of the frequency of students’ use of digital and printed textbook, the advantages and disadvantages, and students’ preferences of reading digital and printed textbooks. The findings indicated that the students perceived the importance of reading both paper and digital textbooks equally for their learning activities. Furthermore, students preferred to read both printed and digital textbooks. None of the students rated one format better than the other.